Implantable Biomaterials for Peripheral Nerve Regeneration–Technology Trends and Translational Tribulations - Sanchez Rezza, Angela; Kulahci, Yalcin; Gorantla, Vijay S.; Zor, Fatih; Drzeniek, Norman M. (Frontiers in Bioengineering and Biotechnology, 2022)
The use of autografted nerve in surgical repair of peripheral nerve injuries (PNI) is severely limited due to donor site morbidity and restricted tissue availability. As an alternative, synthetic nerve guidance channels (NGCs) are available on the market for surgical nerve repair, but they fail to promote nerve regeneration across larger critical gap nerve injuries. Therefore, such injuries remain unaddressed, result in poor healing outcomes and are a limiting factor in limb reconstruction and transplantation. On the other hand, a myriad of advanced biomaterial strategies to address critical nerve injuries are proposed in preclinical literature but only few of those have found their way into clinical practice. The design of synthetic nerve grafts should follow rational criteria and make use of a combination of bioinstructive cues to actively promote nerve regeneration. To identify the most promising NGC designs for translation into applicable products, thorough mode of action studies, standardized readouts and validation in large animals are needed. We identify design criteria for NGC fabrication according to the current state of research, give a broad overview of bioactive and functionalized biomaterials and highlight emerging composite implant strategies using therapeutic cells, soluble factors, structural features and intrinsically conductive substrates. Finally, we discuss translational progress in bioartificial conduits for nerve repair from the surgeon's perspective and give an outlook toward future challenges in the field.